Toxicidade de extratos de Machaerium opacum (fabaceae) em Spodoptera frugiperda (lepidoptera: noctuidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The main pest of the corn crop is the caterpillar Spodoptera frugiperda, and currently the main methods used to control this pest have been chemical insecticides and transgenic plants. The search for alternative methods of control has aroused interest in insecticidal plants. Numerous plant extracts have been studied, since they generally have a broad spectrum of insect-pest control, are relatively specific in their mode of action and cause low environmental impact. Among the families of plants that have been studied for this purpose, the Fabacea family has demonstrated high insecticidal potential. The objective of this work was to evaluate the toxicity of extracts of Machaerium opacum in S. frugiperda caterpillars. The ethanolic, methanolic and hexane fractions of extracts from the leaves of M. opacum were evaluated. In phytochemical prospecting on the leaves of M. opacum, secondary metabolites were identified: flavonoids, triterpenes, anthraquinones, coumarins, tannins and steroids. The different fractions at the different concentrations evaluated did not present differences regarding the attractiveness of S. frugiperda caterpillar in relation to the control treatment. The hexanic fractions promoted antibiosis by reducing the weight of larva and pupa, larval and pupal mortality, prolongation of the adult phase and abnormalities in adults of S. frugiperda in test. These results show the insecticidal potential of extracts of this plant in the control of S. frugiperda.
Keywords: planta inseticida; metabólitos secundários; lagarta-do-cartucho-do-milho; antixenose.; antibiose; insecticidal plant; secondary metabolites; corn-caterpillar; antibiosis; antixenosis; CIENCIAS AGRARIAS